Enhacing Maternal Competence In Preventing Stunting Through Local Food-Based Complementary Feeding: A Quasi-Experimental Study In West Sulawesi, Indonesia - Evawaty; Harli, Kurnia; Adhisty, Weny Anggraini; Fauziah; Nurwahita; Immawanti (Jurnal Kesehatan Manarang, 2025)
Stunting remains a major public health concern in Indonesia, particularly among children under five. A key contributing factor is limited maternal competence, including insufficient knowledge of the appropriate age to introduce complementary feeding, poor understanding of dietary variety, and inconsistent feeding practices. This study aimed to evaluate the effectiveness of two educational interventions—cooking demonstrations and emotional demonstrations (emo-demo)—in improving maternal knowledge, attitudes, and practices regarding local food-based complementary feeding. A quasi-experimental study was conducted in Majene Regency, West Sulawesi, involving 184 mothers of children aged 6–24 months. Participants were randomly assigned to either the cooking demonstration group or the emo-demo group. Data were collected at baseline and during three follow-up time points. Maternal competence was assessed using validated indicators covering knowledge, attitude, and behavior. Data analysis employed repeated measures ANOVA, the Friedman test, and Generalized Estimating Equations (GEE). Both interventions significantly improved maternal competence. However, the cooking demonstration group consistently achieved higher mean scores in all post-intervention assessments (p < 0.001). Improved maternal behavior was positively associated with weight-for-age in children, although no significant associations were found with height-for-age or weight-for-height indicators. Contextual, interactive, and hands-on educational approaches such as cooking demonstrations proved more effective in enhancing maternal competence for stunting prevention. Integrating culturally relevant, food-based learning into community health programs offers a promising and sustainable strategy to improve child nutrition, especially in regions rich in local food resources. Moreover, these educational interventions may also be incorporated into health education curricula at various academic levels to strengthen future health professionals’ competencies in nutrition promotion and stunting prevention.